An investigation on implementations of theoretical whitebox cryptographic solutions - Eshan, Adnan Rahman; Kashfee, Jarin Tasnim Khan; Hasan, Md. Rabib; Islam, Mahmudul (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.